Tosylhydrazine-promoted self-conjugate reduction–Michael/aldol reaction of 3-phenacylideneoxindoles towards dispirocyclopentanebisoxindole derivatives - Pramanik, Sayan; Mukhopadhyay, Chhanda (Beilstein Journal of Organic Chemistry, 2022)
An efficient tosylhydrazine-mediated conjugate reduction of 3-phenacylideneoxindole and sequential Michael/intramolecular aldol reaction is reported under base-catalyzed conditions towards the formation of densely substituted dispirocyclopentanebisoxindole derivatives. The reaction proceeded in a diastereoselective manner to afford four chiral stereocenters. The method also has advantages of wide substrate scope, readily available starting materials and operational simplicity through one pot reaction.
Keywords: chemoselective conjugate reduction; dispirocyclopentanebisoxindole scaffolds; metal-free; one-pot operation; reductive cyclization

(untitled) - Lo, M. M.-C.; Neumann, C. S.; Nagayama, S.; Perlstein, E. O.; Schreiber, S. L. (J. Am. Chem. Soc., 2004)

(untitled) - Zhao, Y.; Liu, L.; Sun, W.; Lu, J.; McEachern, D.; Li, X.; Yu, S.; Bernard, D.; Ochsenbein, P.; Ferey, V.; Carry, J.-C.; Deschamps, J. R.; et al. (J. Am. Chem. Soc., 2013)

(untitled) - Girgis, A. S. (Eur. J. Med. Chem., 2009)

(untitled) - Prasanna, P.; Balamurugan, K.; Perumal, S.; Yogeeswari, P.; Sriram, D. (Eur. J. Med. Chem., 2010)

(untitled) - Murugan, R.; Anbazhagan, S.; Sriman Narayanan, S. (Eur. J. Med. Chem., 2009)

(untitled) - Karthikeyan, K.; Sivakumar, P. M.; Doble, M.; Perumal, P. T. (Eur. J. Med. Chem., 2010)

(untitled) - Kia, Y.; Osman, H.; Kumar, R. S.; Murugaiyah, V.; Basiri, A.; Perumal, S.; Wahab, H. A.; Bing, C. S. (Bioorg. Med. Chem., 2013)

(untitled) - Reddy, B. V. S.; Karthik, G.; Rajasekaran, T.; Sridhar, B. (Eur. J. Org. Chem., 2015)

(untitled) - He, J.; Ouyang, G.; Yuan, Z.; Tong, R.; Shi, J.; Ouyang, L. (Molecules, 2013)

(untitled) - Huang, W.-J.; Chen, Q.; Lin, N.; Long, X.-W.; Pan, W.-G.; Xiong, Y.-S.; Weng, J.; Lu, G. (Org. Chem. Front., 2017)

(untitled) - Kumar, R. S.; Rajesh, S. M.; Perumal, S.; Banerjee, D.; Yogeeswari, P.; Sriram, D. (Eur. J. Med. Chem., 2010)

(untitled) - Liu, Y.-L.; Wang, X.; Zhao, Y.-L.; Zhu, F.; Zeng, X.-P.; Chen, L.; Wang, C.-H.; Zhao, X.-L.; Zhou, J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Liu, D.; Cao, J.; Sun, J.; Liu, R.-Z.; Yan, C.-G. (Org. Lett., 2020)

(untitled) - Zhao, H.-W.; Chen, X.-Q.; Yang, Z.; Tian, T.; Li, B.; Meng, W.; Song, X.-Q.; Pang, H.-L. (RSC Adv., 2015)

(untitled) - Shen, G.-L.; Sun, J.; Yan, C.-G. (RSC Adv., 2015)

(untitled) - Han, W.-Y.; Li, S.-W.; Wu, Z.-J.; Zhang, X.-M.; Yuan, W.-C. (Chem. – Eur. J., 2013)

(untitled) - Wu, H.; Zhang, L.-L.; Tian, Z.-Q.; Huang, Y.-D.; Wang, Y.-M. (Chem. – Eur. J., 2013)

(untitled) - Sun, W.; Hong, L.; Zhu, G.; Wang, Z.; Wei, X.; Ni, J.; Wang, R. (Org. Lett., 2014)

(untitled) - Siva Sankara, C.; Namboothiri, I. N. N. (Org. Lett., 2021)

(untitled) - Tan, F.; Cheng, H.-G.; Feng, B.; Zou, Y.-Q.; Duan, S.-W.; Chen, J.-R.; Xiao, W.-J. (Eur. J. Org. Chem., 2013)

(untitled) - Dai, W.; Jiang, X.-L.; Wu, Q.; Shi, F.; Tu, S.-J. (J. Org. Chem., 2015)

(untitled) - Sun, J.; Sun, Y.; Gong, H.; Xie, Y.-J.; Yan, C.-G. (Org. Lett., 2012)

(untitled) - Sun, J.; Xie, Y.-J.; Yan, C.-G. (J. Org. Chem., 2013)

(untitled) - Shen, G.-L.; Sun, J.; Xie, Y.-J.; Yan, C.-G. (ChemistrySelect, 2016)

(untitled) - Suman, K.; Ramanjaneyulu, M.; Thennarasu, S. (Org. Biomol. Chem., 2017)

(untitled) - Yang, R.-Y.; Sun, J.; Jin, G.; Yan, C.-G. (Mol. Diversity, 2018)

(untitled) - Pramanik, S.; Maity, S.; Ghosh, P.; Mukhopadhyay, C. (Tetrahedron Lett., 2019)

(untitled) - Pramanik, S.; Ray, S.; Maity, S.; Ghosh, P.; Mukhopadhyay, C. (Synthesis, 2021)

(untitled) - Zhou, X.; Li, X.; Zhang, W.; Chen, J. (Tetrahedron Lett., 2014)

(untitled) - Shanthi, G.; Perumal, P. T. (Tetrahedron Lett., 2008)

(untitled) - Ganesh, M.; Rao, M. P.; Mirajakar, S. J. (Asian J. Org. Chem., 2018)

(untitled) - Ganesh, M.; Rao, M. P. (Asian J. Org. Chem., 2018)